PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNINGDAN MODEL PEMBELAJARAN KONVENSIONAL TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARANMATEMATIKA DI KELAS V SDN 068003 P.SIMALINGKAR MEDAN TAHUN PEMBELAJARAN 2018/2019 - SITUMORANG, VALEN ANASTASYA (Unversitas Katolik Santo Thomas, 2019)
This study aims to determine the effect of using Problem Based Learning models on students’ learning outcomes. This research was conducted at SDN 068003 P.Simalingkar Medan in July 2018. The subjects of research were 33 students’. The research method is a One Shot Case Study that is carried out in one class. The instrument used to collecting the data is a multiple choice test. Hypothesis testing is done using the